Types of Epiglottic Collapse in Breathing Sleep Disorder and Their Impact in Clinical Practice - Rachmawati, Elvie Zulka Kautzia; Tamin, Susyana; Fardizza, Fauziah; Yunizaf, Rahmanofa; Putranto, Fikri Mirza; Rizki, Niken Ageng; Wardani, Retno S. (International Archives of Otorhinolaryngology, 2024)
Introduction Obstructive sleep apnea (OSA) is a severe form of sleep-disordered breathing (SDB) that is strongly correlated with comorbidities, in which epiglottic collapse (EC) and other contributing factors are involved.Objectives To evaluate the occurrence of EC in OSA patients through drug-induced sleep endoscopy (DISE) and to determine the factors contributing to EC.Methods A retrospective study of 37 adult patients using medical history. Patients were assessed for laryngopharyngeal reflux (LPR) and lingual tonsil hypertrophy (LTH) using reflux symptom index and reflux finding score (RFS); for OSA using polysomnography, and for airway collapse through DISE. An independent t-test was performed to evaluate risk factors, including the involvement of three other airway structures.Results Most EC patients exhibited trap door epiglottic collapse (TDEC) (56.8%) or pushed epiglottic collapse (PEC) (29.7%). Lingual tonsil hypertrophy, RFS, and respiratory effort-related arousal (RERA) were associated with epiglottic subtypes. Laryngopharyngeal reflux patients confirmed by RFS (t(25) = −1.32, p = 0.197) tended to suffer PEC; LTH was significantly associated (X2(1) = 2.5, p = 0.012) with PEC (odds ratio [OR] value = 44) in grades II and III LTH patients; 11 of 16 TDEC patients had grade I LTH. Pushed epiglottic collapse was more prevalent among multilevel airway obstruction patients. A single additional collapse site was found only in TDEC patients.Conclusion Laryngopharyngeal reflux causes repetitive acid stress toward lingual tonsils causing LTH, resulting in PEC with grade II or III LTH. Trap door epiglottic collapse requires one additional structural collapse, while at least two additional collapse sites were necessary to develop PEC. Respiratory effort-related arousal values may indicate EC.
Keywords: drug-induced sleep endoscopy; epiglottic collapse; laryngopharyngeal reflux; lingual tonsil hypertrophy; obstructive sleep apnea; VOTE classification